Effect of 4-2-1 strategy on achievement of eighth grade students in mathematics - Karim, Asst.L.Bafrin Gharib Ghafoor (Sulaimani Journal for Humanities, 2026)
The aim of the present study is to identify the effect of the 4-2-1 strategy on the achievement of eighth-grade basic education students in mathematics. To achieve the objectives of the study, In order to achieve the objectives of the study, a experimental method was used. The requirements of the study were prepared, which included identifying the scientific content, formulating behavioral objectives, preparing daily lesson plans, and constructing and preparing an achievement test. After confirming the accuracy of the test (82%) and the reliability of the test (0.84), it was found that both were high and acceptable.. The experiment was conducted on a sample of (63) students: an experimental group consisting of (32) students and a control group consisting of (31) students from eighth-grade basic education students at Shad Basic School during the academic year (2024–2025). The two research groups were equivalent in terms of students’ age (calculated in months), Raven’s intelligence test scores, parents’ educational level, and previous year mathematics achievement scores. The researcher taught the experimental group according to the 4-2-1 strategy, while the control group was taught using the traditional method. After the completion of the experiment, the achievement test was administered to both groups. A number of appropriate statistical tools were used, including Chi-square, Pearson correlation coefficient, arithmetic mean, standard deviation, and the t-test, implemented through the SPSS program. The results revealed a statistically significant difference at the significance level (0.05) between the mean scores of the two research groups on the achievement test, in favor of the experimental group. The study's recommendations include implementing the 4-2-1 strategy in the basic education stage in mathematics and establishing training courses for mathematics teachers at all levels to learn about the 4-2-1 strategy.
Keywords: strategy; 421 strategy; achievement; Mathematics